Moisture absorption of composites with interfacial storage. (July 2020) - Guloglu, Gorkem E.; Hamidi, Youssef K.; Altan, M. Cengiz
Abstract: Thermosetting polymer composites are often exposed to wet and humid environments, leading to a considerable reduction in their thermo-mechanical properties. Hence, accurate description of the moisture absorption dynamics, including anomalous effects such as molecular bonding and interfacial storage of moisture, is particularly important. In this study, the hindered diffusion model is extended to include the moisture storage at the interface of impermeable fibers or inclusions within the composite. The model is independent of the reinforcement geometry and can be used for fibrous and spherical reinforcements, or for nanoscale additives. The nondimensional formulation and the analytical solution of the model are shown to yield a nondimensional hindrance coefficient that governs the amount of interfacial moisture storage. This phenomenological parameter is expected to be dependent on the interfacial area available for moisture storage, hence should be correlated with the reinforcement volume fraction. To validate this model, available experimental moisture absorption data for epoxy composites containing APS- and nBS-treated glass spheres at different volume fractions are used. The absorption behaviors exhibited by these composites are shown to be successfully described by the hindered diffusion model for all sphere volume fractions. Moreover, the nondimensional hindrance coefficient and the amount of interfacial moisture storage for both composites are found to be linearly related to the volume fraction of the spheres. These results uncover the underlying relationship between the phenomenological model coefficients and the composite microstructure, further validating the theoretical approach to describe the interfacial moisture storage.